Increasing The Activeness and Achievement of Learning Science (IPA) Students of Class VII B SMPN 3 Sewon Using the Think Pair Share Model for the 2021/2022 Academic Year - Sarjito Sarjito (CV. Rayyan Dwi Bharata, 2023)
This study aims to increase the activity and learning achievement of natural sciences (IPA) using the Think Pair Share learning model. This research is a class action research carried out in two (2) cycles. Each cycle consists of three (3) meetings consisting of two (2) meetings for the learning process and one (1) meeting for achievement tests which are done independently. Each cycle follows the stages of the Kemmis and Taggart models which include four components, namely planning, action, observation and reflection. The data collected in this study is the result of research related to the implementation of learning using the Think Pair Share model on natural science material (IPA). Data collection techniques using test and non-test techniques with descriptive and qualitative approaches. The results of the study show that the use of the Think Pair Share model in natural science learning activities can increase student activity and achievement. In other words, the teaching and learning activities of teachers and students increase as well as student achievement increases. Indicators of the success of this study can be seen from the results of observations and achievement test results after learning is carried out using the